Alokasi Waktu Kerja dan Peran Istri Nelayan dalam Meningkatkan Ekonomi Keluarga di Kelurahan Petoaha Kecamatan Nambo Kota Kendari - Amir, Fitriah; Hamzah, Awaluddin; Limi, Muhammad Aswar (Department of Agribusiness, Halu Oleo University, 2019)
This research aimed (1) To describe the working time allocation and role of the fisherman’s wife as a fish seller for activities in the household, social activities and economic activities, (2) To know the contribution of fisherman's wife in improving family economy and (3) To know the relation between family income and working time allocation of fisherman’s wife. This research was conducted in the Petoaha, the districts of Nambo. The population of this research was the entire of the fisherman's wife of Petoaha, the districts of Nambo as a fish seller. Sample determination using purposive sampling technique. The number of samples is determined using Slovin formula and based on the calculation result using the formula, the total sample is 43 respondents. The results of this research showed that the average allocation of working time and the role of fisherman’s wife for household activities is 66.56%, social activities 1.29% and economic activities 14.94%. The average income contribution of fishermen's wife to family income is 42%. The relationship between family income and the fisherman’s wife working is the family income in the lower category, the allocation time of fisherman’s wife in economy activity increasing